The effect of credit risk management on financial sustainability of microfinance institutions in Kenya - Kanake, Joyce K. (Strathmore University, 2014)
Microfinance has been considered to be a powerful tool to fight poverty through the provision of basic financial services such as credit, savings, insurance, and transfer of funds. However, the credit support granted to such micro businesses usually lacks collateral, it is imperative that the management of such credit services be sound in order to mitigate the credit risks involved. Credit risk management determines the success and survival of the MFls. The performance of the MFI is crucial because it boils down to the long term survivaL The purpose of this research was to find out the effect of credit risk management indicators on financial sustainability of MFls in Kenya. Data was analyzed from 37 MFls who were registered with AMFI by 2012 in Kenya. A linear regression model was used where financial self-sufficiency was the dependent variable while predictor variables were portfolio at risk, risk cover ratio, loan loss provision, number of borrowers and total assets both as control variables for breadth of outreach and size of the organization respectively. The study found out that portfolio at risk and loan loss provision both had a significant negative effect on financial sustainability meaning increase in portfolio at risk and loan loss provision will reduce financial sustainability of the microfinance institution. Risk coverage ratio and number of borrowers had a positive impact on financial sustainability but not statistically significant. However total assets had a significant positive impact meaning increase in total asset would increase financial sustainability. The study therefore established that credit risk management affect financial sustainability of microfinance institutions in Kenya. Meaning that in order to increase financial sustainability of MFIs there is need to properly manage credit risk because according to the study, credit risk management significantly affects financial sustainability of microfinance institutions.
Submitted in partial fulfillment of the requirements for the Degree of Master of Commerce
Keywords: Credit risk management; credit; Microfinance; Finance; Kenya